2019
DOI: 10.3390/electronics8111370
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Image Inpainting Based on Multi-Scale Neural Network

Abstract: Although image inpainting based on the generated adversarial network (GAN) has made great breakthroughs in accuracy and speed in recent years, they can only process low-resolution images because of memory limitations and difficulty in training. For high-resolution images, the inpainted regions become blurred and the unpleasant boundaries become visible. Based on the current advanced image generation network, we proposed a novel high-resolution image inpainting method based on multi-scale neural network. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In the experiments, COCO and VOC datasets which included 135,414 images as training data and 200 images as testing data were selected to evaluate the proposed method. The results show that the PSNR and SSIM of the proposed method were higher than the PSNR and SSIM of other methods [54].…”
Section: Measurement and Denoising Techniquesmentioning
confidence: 77%
See 1 more Smart Citation
“…In the experiments, COCO and VOC datasets which included 135,414 images as training data and 200 images as testing data were selected to evaluate the proposed method. The results show that the PSNR and SSIM of the proposed method were higher than the PSNR and SSIM of other methods [54].…”
Section: Measurement and Denoising Techniquesmentioning
confidence: 77%
“…) to analyze and denoise measured data in a variety of applications and services (e.g., wind speed prediction, air quality prediction, underground mine applications, neural audio caption, etc.). Several practical experiments were given in these articles, and the results indicated that the performance of the improved deep learning methods could be higher than the performance of conventional machine learning methods [43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…However, the non-local module was originally designed for the task of classification and this operation is not sufficient to significantly improve the performance of our framework. In addition to using the attention mechanism to obtain non-local information, a pre-trained model of the VGG network [ 22 ] has been wildly adopted to extract non-local features by calculating style loss. The essence of style loss is learning the relationship of existed and unknown regions by using the Gram-matrix to calculate the pixel relevance.…”
Section: Related Workmentioning
confidence: 99%
“…The ChestX-ray image of a patient needs to be read by a senior radiologist for at least 10 min to make a diagnosis and different doctors can make inconsistent diagnoses of the same ChestX-ray image, which means that the results are affected by the cognitive ability of the radiologist, subjective experience, fatigue and other factors [2]. Computer-aided diagnosis (CAD) can overcome the deficiencies of radiologists, make Recently, benefitting from deep learning techniques [6], computer vision [7] has had remarkable success in the fields of target detection [8], image classification [9,10] and image inpainting [11], for example. This notable progress has led to the development of many medical image processing applications, including disease classification [12], lesion detection or segmentation [13][14][15], registration [16], image annotation [17,18] as well as other examples [19].…”
Section: Introductionmentioning
confidence: 99%